2016
DOI: 10.1152/ajpendo.00502.2015
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell dedifferentiation, reduced duct cell plasticity, and impaired β-cell mass regeneration in middle-aged rats

Abstract: Téllez N, Vilaseca M, Martí Y, Pla A, Montanya E. ␤-Cell dedifferentiation, reduced duct cell plasticity, and impaired ␤-cell mass regeneration in middle-aged rats. Am J Physiol Endocrinol Metab 311: E554 -E563, 2016. First published July 12, 2016 doi:10.1152/ajpendo.00502.2015.-Limitations in ␤-cell regeneration potential in middle-aged animals could contribute to the increased risk to develop diabetes associated with aging. We investigated ␤-cell regeneration of middle-aged Wistar rats in response to two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Interestingly, gastrin treatment was only found effective in combination with other proliferative stimuli, such as GLP-1, DPP-4 inhibitors, epidermal growth factor, previous duct ligation or partial pancreatectomy (25,27,28,29,34). The proposed molecular mechanism of gastrin's action on beta-cell regeneration includes an induction of differentiation of ductal cells into endocrine cells, as suggested by an increased expression of endocrine markers, such as neurogenin 3 or nkx6.1 (35,36). Furthermore, a recovery of insulin expression, as well as increased beta-cell replication, has been described in alloxan-induced diabetic mice (37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, gastrin treatment was only found effective in combination with other proliferative stimuli, such as GLP-1, DPP-4 inhibitors, epidermal growth factor, previous duct ligation or partial pancreatectomy (25,27,28,29,34). The proposed molecular mechanism of gastrin's action on beta-cell regeneration includes an induction of differentiation of ductal cells into endocrine cells, as suggested by an increased expression of endocrine markers, such as neurogenin 3 or nkx6.1 (35,36). Furthermore, a recovery of insulin expression, as well as increased beta-cell replication, has been described in alloxan-induced diabetic mice (37).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that after partial pancreatectomy in adult rats, pancreatic-duct cells undergo a reproducible dedifferentiation and expansion forming transient areas composed of proliferating ductules; these foci of regeneration subsequently recapitulate aspects of embryonic pancreatic differentiation to form new pancreatic lobes with new islets (Bonner-Weir et al, 1993; Li et al, 2010). Recent data has shown that by 1 year of age there was a loss of this plasticity of the pancreatic ducts resulting in less neogenesis (Tellez et al, 2016). In these older rats, without the neogenesis, the β cell mass did not increase after Px even though β cell replication and apoptosis frequency did not differ with that of 1 month old and individual cell size had similar increases.…”
Section: Classic Islet Regeneration Modelsmentioning
confidence: 99%
“…Px : Removal of 60~90% of the adult rat pancreas through Px administration induces extensive pancreatic regeneration with formation of new lobes and islets, and proliferation of acinar cells. The Px model has been used to study β cell neogenesis and replication (86, 127, 128). PDL : PDL is defined as surgical ligation of the pancreatic duct at the level of the pylorus.…”
Section: Rodent Models For Study Of β Cell Regenerationmentioning
confidence: 99%